Socio-Ecological Disruptions at Critical Periods During Development Alter Stress Responses and Hippocampal Dendritic Morphology of Prairie Voles: Implications for Social Monogamy - Al-Naimi, Omar A. S.; Delvalle, Jose R.; Carryl, Sophia S.; Rodriguez, Natalia A.; Aliou, Fayeza; Cambi, Monica; Bamshad, Maryam (Frontiers in Ecology and Evolution, 2018)
Emotions are often associated with the evolution of monogamy. For example, fear of cuckoldry has been recently proposed as the driving force for human monogamy. We used prairie voles (Microtus ochrogaster) as a model of human behavior to study how stress reactivity is shaped by socio-ecological disruptions experienced as neonates and as subadults. We hypothesized that social disruptions would have a greater impact on the vole’s stress levels than ecological disruptions, and that females would be more susceptible to the experience than males. At six days postpartum, the housing conditions were manipulated to have offspring raised by: 1. both parents under a protective cover (NoDisrupt); 2. both parents uncovered (EcoDisrupt); 3. mother alone covered (SocDisrupt); 4. mother alone uncovered (SocEcoDisrupt). To experience disruptions as subadults, offspring were weaned then housed either alone (Isolate) or with a same-sex sibling (Social). As adults, each offspring was placed in an open-field arena and tested over three consecutive days to measure its behavior in response to an empty space (Day1), a same-sex vole in a container (Day2), and an empty container (Day3). The brain of a subgroup of subjects was processed for Golgi staining to assess the impact of disruptions on hippocampal dendritic morphology in adulthood. Males that experienced social disruption in early life displayed lower stress levels on Day2 of testing than males and females in other groups. This effect was only evident in males that did not experience social disruptions as subadults. Socio-ecological disruptions at postpartum had an unanticipated impact on the hippocampus of the voles. The apical dendrites of the CA3 neurons in male and female voles that experienced either social or ecological disruptions in early life and remained socially isolated as subadults were longer than those in undisturbed voles. Our results suggest that social disruptions experienced in early life modulate the male’s stress-related behaviors and may thus influence his monogamous tendencies. Exposure to disruptions may also impact the memory circuits of the brain that monogamous animals use to make mating decisions.